Elevated CO2 does not improve seedling performance in a naturally regenerated oak woodland exposed to biotic stressors - Mayoral, Carolina; Ioni, Susanna; Luna, Estrella; Crowley, Liam M.; Hayward, Scott A. L.; Sadler, Jon P.; MacKenzie, A. Robert (Frontiers in Forests and Global Change, 2023)
Introduction Insect herbivores and biotrophic pathogens are major stressors influencing natural regeneration in woodlands. Information on the effect of elevated CO2 (eCO2) on plant-insect-pathogen interactions under natural conditions is lacking. Methods We studied the effects of eCO2 on leaf-out phenology, as well as on levels of insect herbivory and powdery mildew (PM), i.e., reduction of leaf photosynthetic material. We then assessed the combined impacts of these biotic stressors and eCO2 on seedling photosynthesis and growth. A total of 92 naturally recruited and 114 potted seedlings of 5 temperate tree species (Quercus robur, Acer pseudoplatanus, Corylus avellana, Crataegus monogyna, and Ilex aquifolium) within a mature oak woodland were studied. Results We found that eCO2 advanced leaf-out phenology and was a significant explanatory variable for growth and physiological performance in potted seedlings. Potted oak seedlings experienced 11-fold higher tissue loss from insect herbivory than natural seedlings. The earliest leaf-flushing species, hawthorn, and the evergreen holly were resistant to insect attack and were not affected by PM. Oak was defoliated most but showed the highest regeneration capacity. Hazel was more resistant to PM infection than oak and sycamore. Despite being highly infected by PM, sycamore was less affected than oak. The more vigorous sycamore and oak seedlings suffered more severe PM disease. Conclusion No evidence emerged that eCO2 enhances natural regeneration under biotic stress for any of the species studied.